2022
DOI: 10.3390/agronomy12020306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glucosinolates on the Growth and Development of Helicoverpa armigera Larvae and the Expression of Midgut Sulfatase Genes

Abstract: The plant–pest interaction and its mechanisms are a novel research direction for pest control. They provide molecular targets for developing new pesticides and targeted control measures to control insect herbivores. Glucosinolate is a large family of secondary substances found in cruciferous plants that are harmful to herbivorous insects. Specialist herbivores have developed specific anti-defense genes and detoxifying mechanisms against glucosinolate from the host plant, but how generalist herbivores respond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, with the increasing concentration gradient, the indicators did not continue to decrease and even showed improvement at the higher concentration of 0.4% GLS (Li et al, 2022). et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, with the increasing concentration gradient, the indicators did not continue to decrease and even showed improvement at the higher concentration of 0.4% GLS (Li et al, 2022). et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, lower concentrations of GLS had a greater impact on H. armigera , consistent with our prior research, the study showed that the growth and development indicators of H. armigera declined or were delayed as GLS concentrations increased (0.004%–0.04%). However, with the increasing concentration gradient, the indicators did not continue to decrease and even showed improvement at the higher concentration of 0.4% GLS (Li et al., 2022). Furthermore, there are numerous additional experiments on GLS–insect interactions, indicating that insect growth and developmental parameters do not demonstrate proportionality or inverse proportionality with the concentration or composition of GLS (Badenes‐Perez et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…nitriles, thiocyanates and isothiocyanates). 15,[19][20][21] GLSs and their breakdown products can be deterrent to generalist insects 22 and/or may attract their natural enemies, 23 but they are also palatable and attractive to insects specializing in the Brassicaceae family. 24,25 For instance, indole GLSs serve as important cues involved in Plutella xylostella (diamondback moth), a Brassica-specialist acceptance of host plants for oviposition.…”
Section: Introductionmentioning
confidence: 99%